Decision-Making of Fredholm Operator on a New Variable Exponents Sequence Space of Supply Fuzzy Functions Defined by Leonardo Numbers - Alshabhi, Salah H.; Mohamed, OM Kalthum S. K.; Mohammed, Mustafa M.; Khalid, Thwiba A.; Mustafa, Arafa O.; Magzoub, Mona; Taha, Khdija O.; Bakery, Awad A. (Contemporary Mathematics, 2024)
In this article, we will use a weighted regular matrix formed by Leonardo numbers and variable exponent sequence spaces to build a new stochastic space. We have proposed various geometric and topological structures for this new space, as well as the multiplication operator that operates on it.